(untitled) (ENTHYMEMA, 2018)
Review of the conference "The Interpretation of Nizami’s Cultural Heritage in the Modern Period" organized by the Nizami Ganjavi International Centre and Azerbaijan Comparative Literature Association. Baku, Azerbaijan, 13-14th March 2018.